Spiritual Emotional Freedom Technique (SEFT) Improves Psychological Well-Being of New Female Students in an Islamic Boarding School - Ibtisama Manissa; Retno Twistiandayani; Mono Pratiko Gustomi; Natalia Christin Tiara Revita (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2026)
Background: Psychological well-being is an important component of mental health that indicates an individual's ability to function optimally in daily life, have life satisfaction, and be able to face stress and life challenges adaptively. New students at Islamic boarding schools are in a transition period that is vulnerable to psychological well-being disorders due to the demands of environmental adaptation, changes in lifestyle, and academic and social pressures. Objective: The general objective of this study is to explain the effect of SEFT therapy on the level of Psychological Well Being of new students at Islamic boarding schools. Method: The research design was a quasi-experimental pre-post test without control. With a sample of 54 female students who had just entered Al-Hadi Islamic boarding school, spesific Annur boarding house. Research instrument questionnaire for Ryff psychological well-being. Results: The Paired Sample T-Test statistical test obtained a ρ value = 0.000 (ρ sign <0.05), meaning that there is an effect of SEFT therapy on improving psychological well-being. Conclusion: With this background, this study aims to determine the effect of SEFT therapy on the level of psychological well-being in new students at Islamic Boarding Schools, so that the results of the study are expected to provide scientific contributions to holistic nursing practice and an understanding of strategies for improving mental health among students.